RANCANG BANGUN SISTEM PENGAPIAN SEMI ELEKTRONIK DOUBLE TRIGGER SEBAGAI PENGEMBANGAN SISTEM PENGAPIAN KONVENSIONAL - Holik, Hasan; Mujianto, Haris; Rubiono, Gatut (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2016)
Technology development has negative impact for convensional automotive product.Electronic system has lower exhaust emission than convensional system. Convensional system still can develop in order to minimize environmental risk. The development of convensional system can be done by changing the system into semi electronic. It is need an addition of CDI DC system and replacement of switch between pulser and trigger. Trigger must made at distributor shaft with high precision working. This research is aimed to develop convensional ignition system into semi electronic to increase the performance of automotive engine.